“Children on the Move” as a Vulnerable Population - Bogetić, Dragica R.; Jugović, Aleksandar L. (Sociološki pregled, 2019)
The notion of “children on the move” is relatively new in the scientific and political sense. The goals of this paper are the conceptualization of the notion and categories of “children on the move”, the analysis of risk factors and the consequences for the well-being of children created by forced migrations and the establishment of a theoretical framework for understanding this phenomenon. In the paper, analysis and synthesis are used as general scientific methods. “Children on the move” represent a vulnerable population which is in many ways exposed to different types of risks for their safety, health and socio-emotional development. Particular challenges for the protection of “children on the move” concern the realization of the right to non-discrimination, the right to the best interest, the right to life, survival and development and the right to participation. The social policy towards “children on the move” should be multidimensional and multisectoral.
Keywords: children on the move; social vulnerability; children’s rights; social risks